2023
DOI: 10.1002/acs.3554
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐adaptive practical prescribed‐time control for pure‐feedback nonlinear systems without accurate initial errors

Abstract: Summary This article studies the problem of practical prescribed‐time tracking for pure‐feedback nonlinear systems, where the transient behavior, steady‐state precision, settling time as well as the rate of convergence can be preset irrespective of initial conditions. With the help of a time‐dependent function and a state‐dependent function, a simple coordinate transformation is established to construct a neuro‐adaptive controller to achieve the tracking purpose. In particular, the proposed controller does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…[13][14][15] It is well established that adaptive control, endowed with online estimation/learning capabilities through identification/compensation mechanisms, is highly effective in dealing with unknown parameters and improving system performance. [16][17][18][19] Existing research has shown that adaptive event-triggered control can improve the transient performance of closed-loop systems while reducing data transmission by setting suitable triggering conditions. [20][21][22][23][24][25][26] Based on the different triggering objects, these existing results are generally divided into two categories: signal transmission triggering 20,21 and parameter estimation triggering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] It is well established that adaptive control, endowed with online estimation/learning capabilities through identification/compensation mechanisms, is highly effective in dealing with unknown parameters and improving system performance. [16][17][18][19] Existing research has shown that adaptive event-triggered control can improve the transient performance of closed-loop systems while reducing data transmission by setting suitable triggering conditions. [20][21][22][23][24][25][26] Based on the different triggering objects, these existing results are generally divided into two categories: signal transmission triggering 20,21 and parameter estimation triggering.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that adaptive control, endowed with online estimation/learning capabilities through identification/compensation mechanisms, is highly effective in dealing with unknown parameters and improving system performance 16–19 . Existing research has shown that adaptive event‐triggered control can improve the transient performance of closed‐loop systems while reducing data transmission by setting suitable triggering conditions 20–26 .…”
Section: Introductionmentioning
confidence: 99%
“…The convergence rate and the final tracking error range, two crucial metrics for assessing the controller, must frequently be taken into account when developing a controller. The tracking error needs to converge to a specified precision within a given period for several application scenarios that have higher criteria for safety and reliability, such as target interception, spacecraft docking, and auto parts assembly [1,8]. The latest results of prescribed time control [9][10][11][12][13] solve the problem of system stability in a limited time.…”
Section: Introductionmentioning
confidence: 99%